Calotropis procera (leaves) supplementation exerts curative effects on promoting functional recovery in a mouse model of peripheral nerve injury - Shamaila Zafar (Food Science & Nutrition, 2021)
Abstract Peripheral nerve injuries are among those complicated medical conditions, which are still waiting for their highly effective first‐line therapies. In this study, the role of Calotropis procera crude leaves was evaluated at different doses for their effectiveness in improving functional recovery following sciatic nerve injury‐induced in the mouse model. Thirty‐two healthy albino mice were divided into four groups as Normal chow group (control, n = 8) and C. procera chow groups (50 mg/kg (n = 8), 100 mg/kg (n = 8) and 200 mg/kg (n = 8)). Behavioral analyses were performed to assess and compare improved functional recovery along with skeletal muscle mass measurement in all groups. Serum samples were analyzed for oxidative stress markers. Results showed that C. procera leaves at dose‐dependent manner showed statistically prominent (p < .05) increase in sensorimotor functions reclamation as confirmed by behavioral analyses along with muscle mass restoration and prominent decline in TOS and momentous increase in TAC along with the augmented activity of antioxidative enzymes.